(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Abstract: Outcome-Based Education (OBE) means emphasizing on results. OBE practitioners begin by determining the knowledge, competencies, skills and abilities that they want students to demonstrate as and when they complete their schooling and confront the challenges of the real world. OBE is a way of designing, delivering and documenting instructions in order to achieve desired goals and outcome. During 1980s Americans reported that schools were in a serious trouble and many children were not being able to learn. In reality, the fresh mind and the eagerness to learn in children makes them look and learn as much as possible. They learn how to talk, walk, ride bicycles, and make a bond with parents and teachers and so much more. Academic institutions are solely responsible for designing curriculum for children. Numerous studies reported that schools are not being able to implement curriculum and the obvious resolution to that problem is educational restructuring which is broadly known as “Outcome Based Education” (OBE). The present research article is an attempt to analyse critically the “Outcome Based Education” (OBE) and try to introduce an alternative to OBE, which is THE PROCEDURAL-INQUIRY MODEL.